Academic, Leadership, and Demographic Characteristics of Orthopaedic Sports Medicine Division Chiefs in the United States. (January 2022) - Maqsoodi, Noorullah; Mesfin, Addisu; Li, Xinning
Abstract : Introduction: Division chiefs (DCs) play an integral role within the department, making critical decisions and helping shape the future of both the division and the department. This study aimed to investigate the demographic characteristics and scholarly work of DCs in academic orthopaedic sports medicine division in the United States. Methods: Orthopaedic residency programs at academic centers were identified using the Association of American Medical Colleges' Electronic Residency Application Service. DCs were identified using the program's respective websites where data points such as sex, race/ethnicity, fellowship training institution, time since graduating fellowship, academic rank, number of degrees, and additional leadership titles were collected. Scopus database was used to determine h-indices. Results: From the 191 programs identified, 100 had a DC for the sports medicine subspecialty division, and 66 programs offered a sports medicine fellowship. Most DCs (96%) were men. The racial/ethnic demographics of the DCs were mostly White (86%), followed by Asian (11%), African American (1%), Hispanic/Latino (1%), and mixed ethnicity (1%). On average, the DCs were 19.6 years past their fellowship completion. The average h-index was 21.2. Many (48%) had an academic rank of professor, 28% associate professor, and 12% assistant professor. Four held additional graduate degrees. The fellowship programs that trained the most DCs were Hospital for Special Surgery (11), Kerlan Jobe Orthopaedic Clinic (8), University of Pittsburgh (7), American Sports Medicine Institution (5), Cleveland Clinic (5), Cincinnati Sports Medicine (4), Massachusetts General Hospital (4), and Steadman Hawkins Clinic (4). Discussion: DCs in academic orthopaedic surgery plays a crucial role in the department and is a topic that is understudied. A lack of diversity exists among DCs in academic Sports Medicine in orthopaedics. The position is held predominately by White men with a rank of either full or associate professor and extensive leadership experience. More efforts are needed to increase the diversity of sports medicine leadership within academic orthopaedic programs in the United States.